Creation of an Electronic Textbook for University Students - M.G, Sergeeva (2020)
The need for e-learning in modern Russia is caused by the rapid development of informatization, digitalization, information and communication technologies, the creation of a global environment for mutual integration of cultures and disciplines, as well as the formation of open continuous education, which is the basis of a post-industrial (information) society. These processes stimulate an active search for creative educational practices that meet the requirements of the information society. A modern specialist must have a certain amount of knowledge that will allow him to learn constantly, improve his skills and abilities, self-develop and self-actualize in order to keep up with the time of changes in the information society. In the framework of the modern educational paradigm, the student is considered as a subject of knowledge, not an object of pedagogical influence. In the early – mid-2010s, this is actively promoted by electronic learning (e-learning, EL), which should be used in various educational organizations. E-learning allows integrating into the world scientific community, becoming subjects of interaction between cultures, including the exchange of spiritual values. Implementation of EL is one of the key tasks in the context of modernization of national education. The term “electronic learning” is translated into Russian in various ways. The most popular options are: “distance learning/education”, “mobile learning”, and “virtual learning”. The European Commission interprets “e-learning” as “using new multimedia and Internet technologies to improve the quality of learning by improving access to resources and services, as well as remote knowledge sharing and collaboration”. In this study, the concept of “e-learning” will correspond to the phrase “electronic learning”. This is an educational process based on interactive electronic means of storing and providing information: the Internet, corporate networks, and CDs.